2018
DOI: 10.21273/hortsci13066-18
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tomato Bruising by Mechanical Impact Force Using Multivariate Analysis

Abstract: Fresh fruit bruising caused by mechanical impact is the most problematic effect of mechanical postharvest processing of tomatoes. The conventional postharvest process of tomato fruit (Solanum lycopersicum L.) handling was surveyed from harvest to shipping preparation at a farm in Toechon in the Republic of Korea. Acceleration sensors located on the harvest boxes and fruit skin showed that the most severe impact forces (>10 g) occurred while fruit was moved in and out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…As observed, the firmness of the tomato declined gradually at both storage conditions for all impact levels, however, the reduction was higher in the tomatoes bruised from the highest level stored at room temperature. Similar results were recorded by Cui et al [2], where the firmness loss in the bruised tomato increased with the increase in the drop impact height. Additionally, Buccheri and Cantwell [11] recorded higher firmness reduction with high (99 cm) drop impact levels compared to 33 cm and 66 cm drop impact levels, respectively.…”
Section: Effect On the Firmnesssupporting
confidence: 90%
See 2 more Smart Citations
“…As observed, the firmness of the tomato declined gradually at both storage conditions for all impact levels, however, the reduction was higher in the tomatoes bruised from the highest level stored at room temperature. Similar results were recorded by Cui et al [2], where the firmness loss in the bruised tomato increased with the increase in the drop impact height. Additionally, Buccheri and Cantwell [11] recorded higher firmness reduction with high (99 cm) drop impact levels compared to 33 cm and 66 cm drop impact levels, respectively.…”
Section: Effect On the Firmnesssupporting
confidence: 90%
“…Experimentally, Hussein et al [13] showed a positive correlation between the drop height and BA occurrence in pomegranate. Regarding storage conditions, Cui et al [2] found that bruising incidence in tomatoes is less severe as temperatures are reduced. Table 1 presents the final BA model ( 1) which includes all the independent variables.…”
Section: Effect On Bruise Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The surrounding environment has a direct impact on these changes, which results in the loss of water, texture, color, and nutrients. Therefore, product quality suffers, resulting in lower sale prices and losses for growers [ 1 ]. Strawberries (Fragaria ananassa) are a popular fruit all over the world due to their luscious flesh and distinct flavor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout postharvest operations like harvesting, handling processing, storing, and transporting, fresh produce is subjected to different external forces. Therefore, this reduces product quality and decreasing sale prices as well as losses to the orchardists and growers [4]. Transportation is an essential process during the postharvest supply chain of any fresh produce [5].…”
Section: Introductionmentioning
confidence: 99%